Keadilan, Demokrasi dan HAM dalam Perspektif Pentakosta - Andreas Sese Sunarko (STTI Harvest Semarang, 2019)
Justice, democracy and human right are crucial instruments of a modern country where the implementation should consider the equity and run together as unity. Modern country that is able to implement those instruments consistenly will become a souvereint authority, gain economically prosperity and have a humanly dignity. However, in the real practice of those instruments, a dichotomy occured with arguing about Western and Eastern democracy. Due to the unsolved differentiation problems for the practice of democracy, there are some chlases in law enforcement, which bring a negative impact such asa human right violation. Despite of the existence of many concepts of justice, democracy and human right, the author are intending to analyse from another persepective, Pentacostal perspective. This analysis aims to a fresh point of view that will bring a positive impact for the implementation of justice, democracy and human rights.Abstrak: Keadilan, Demokrasi dan HAM adalah merupakan instrumen-instrumen penting dari sebuah negara modern, dimana dalam pelaksanaannya secara ideal harus berjalan bersama-sama dan tidak boleh berjalan secara parsial.a Negara modern yang mampu menjalankan instrumen-instrumen ini secara konsisten akan menjadi negara yang berwibawa secara kedaulatan dan sejahtera secara ekonomi dan bermartabat dari sisi kemanusiaan. Dalam prakteknya seringkali terjadi benturan-benturan kepentingan dari para pemangku pentingan yang pada akhirnya membuat kurang efektifnya penegakan hukum yang melahirkan ketidakadilan dan ketidakadilan ini berimplikasi pada terjadinya pelanggaran HAM. Terlepas dari adanya banyak konsep tentang Keadilan, Demokrasi dan HAM maka penulis akan mengkajinya dalam perspektif yang berbeda yaitu dari perspektif Pentakosta. Harapannya adalah dari perspektif Pentakosta ini nantinya akan memberikan dampak bagi pelaksanaan Keadilan, Demokrasi dan HAM secara universal.